2023
DOI: 10.3389/fnmol.2023.1106765
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with Sigma1R and A2AR agonists fails to inhibit cocaine self-administration despite causing strong antagonistic accumbal A2AR-D2R complex interactions: the potential role of astrocytes

Abstract: Previous studies have indicated that acute treatment with the monoamine stabilizer OSU-6162 (5 mg/kg), which has a high affinity for Sigma1R, significantly increased the density of accumbal shell D2R-Sigma1R and A2AR-D2R heteroreceptor complexes following cocaine self-administration. Ex vivo studies using the A2AR agonist CGS21680 also suggested the existence of enhanced antagonistic accumbal A2AR-D2R allosteric interactions after treatment with OSU-6162 during cocaine self-administration. However, a 3-day tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The astrocytes in dominance, can modulate blood flow and mediate transfer of mitochondria to neurons and is the major source of cholesterol (Siracusa et al, 2019). It has become increasingly clear in recent years that integrative receptor-receptor and receptor-protein interactions can exist also in the astrocytes potentially altering the affinity and density of these heterocomplexes (Cervetto et al, 2017;Narvaez et al, 2020;Borroto-Escuela et al, 2023) as previously demonstrated in neurons (Borroto-Escuela et al, 2012, 2014, 2017c, 2018bChruscicka et al, 2019;Di Palma et al, 2020;Chruscicka et al, 2021;Romero-Fernandez et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The astrocytes in dominance, can modulate blood flow and mediate transfer of mitochondria to neurons and is the major source of cholesterol (Siracusa et al, 2019). It has become increasingly clear in recent years that integrative receptor-receptor and receptor-protein interactions can exist also in the astrocytes potentially altering the affinity and density of these heterocomplexes (Cervetto et al, 2017;Narvaez et al, 2020;Borroto-Escuela et al, 2023) as previously demonstrated in neurons (Borroto-Escuela et al, 2012, 2014, 2017c, 2018bChruscicka et al, 2019;Di Palma et al, 2020;Chruscicka et al, 2021;Romero-Fernandez et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…Populations of astroglia are important targets for dopaminergic and noradrenergic volume transmission through their contents of dopamine and noradrenaline receptors, including contents of heteroreceptor complexes like A2AR–D2R heterocomplexes ( Cervetto et al, 2017 , 2023 ; Pelassa et al, 2019 ). The monoamine including also serotonin receptors modulate key functions of the astroglia, including microglia ( Fuxe et al, 2012 ; Cervetto et al, 2017 ; Fuxe and Borroto-Escuela, 2018 ; Narvaez et al, 2020 ; Borroto-Escuela et al, 2023 ).…”
Section: Volume Transmission Of Chemical Informationmentioning
confidence: 99%
“…This important technique (PLA) was developed by Fredriksson, Gullberg, Söderberg and colleagues [58,59]. For recent work on the analysis and quantitation of the GPCR heterocomplexes with in situ PLA (see [57,[60][61][62][63][64][65][66][67][68][69][70][71]).…”
Section: On the Existence Of Gpcr Homo-and Heteroreceptor Complexesmentioning
confidence: 99%
“…In current procedures, the receptor complexes appear as red blobs with a diameter of 0.5 to 1.5 um and their density in sampled fields is determined using confocal laser microscopy. The assay is performed in combination with a Neuro-ChromPan neuronal marker antibody-Alexa488, giving a green fluorescence to the neurons and enabling the study of the link of the red blobs to the neurons [61][62][63][64][65]. Based on different types of glial markers, the link of the red blobs to glial cells can also be established.…”
Section: On the Existence Of Gpcr Homo-and Heteroreceptor Complexesmentioning
confidence: 99%
“…Cocaine-induced reorganization of D2R-S1R complexes may in turn contribute to the formation of adenosine 2A receptor (A2AR)-D2R-S1R heterocomplexes; this is interesting as A2AR agonists have anti-cocaine properties. However, a recent study reported that combined treatment with S1R and A2AR failed to inhibit cocaine self-adminstration [ 90 ], highlighting the need for further work to understand these interactions and their role in psychostimulant outcomes and behaviors. [ 75 , 91 ].…”
Section: S1r As a Modulator Of The Rewarding Properties Of Drugs Of A...mentioning
confidence: 99%